Solid waste management in barangay UP Campus assessment of practices and initiatives - Longidare, Hilda P.; Chaves, Carmeli Marie C. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
Solid waste management is a critical consideration with the rapid urbanization-taking place, globally. According to the UNEP 2015 report, developed countries produce a higher rate of solid waste per person per year than developing countries. But there is a significant decline, which has been projected over the coming decades because waste production in other places has been growing, with substantial increases expected first in Asia and then Africa. It is expected that the generation of municipal solid waste in many cities of Asia and Africa will double within 15-20 years. Economic growth in the Philippines coupled with rapid growth in population has resulted in the need for solid waste management as one of the major environmental challenges, Quezon City, being one of the faster growing cities in the Philippines, is faced with many urban challenges including solid waste management. There is a need to understand how planning can help improve solid waste practices in the Philippines. This study focuses on the smallest political unit, which is the barangay, as a case study in order to describe and assess the current practices in the solid waste management process at the municipal level, and proposes planning and policy measures to improve it. The study applies the Integrated Sustainable Waste Management (ISWM) approach to assess the practices and initiatives of solid waste management in Barangay UP Campus. This ISWM system contains essential elements, which are : source reduction, waste transportation, recycling and composting, and landfill. The research identified that the most produced wastes in Barangay UP Campus, are a rich resource for recycling and that awareness of segregation of waste material is high. However,there is no strict implementation due to a lack of monitoring, standardized trash facilities, and signage. The common waste disposal option is that of placing wastes at points of collection for pick-up by a responsible authority. But, since the actors in solid waste management are working independently of each other, there is no common record or database of the total quantity of Solid waste generated in Barangay UP Campus. The study found that largely the waste management system in Barangay UP Campus, follows good practices in waste collection and disposition. But there is a need to improve recycling and composting practices. Moreover, its weakness lies in the monitoring and implementation of rules and regulations of solid waste management through reinforcement of the institutional and financial capacity of solid waste management system.In order to enhance the waste collection system the study recommends the establishment of one integrated collection system, with its own facilities, personnel, and financial capacity. Awareness coverage should be a constant, and the community should be encouraged to establish compost pits in their compound in order to reduce waste collection for disposal at a landfill. Increased investment in solid waste management facilities and improved locations for waste collection points as well is recommended.
Thesis (M.S. Regional and Development Planning)--University of the Philippines Diliman
Keywords: Refuse and refuse disposal -- Philippines -- Quezon City; Integrated solid waste management -- Philippines -- Quezon City; Communities -- Philippines -- Quezon City